An Experimental Study on the Treatment of Engineering Waste Slurry by Using Agent Conditioning-Combined Pressure Filtration. (14th February 2022) - Wu, Yajun; Zhou, Rong; Lu, Yitian; Zhang, Xudong; Lu, Jiansheng
Abstract : Taking the waste high-moisture slurry produced at a construction site in Shanghai as the research object, the pressure filtration effect of the slurry under the condition of agent conditioning was studied. First of all, the geotechnical characteristics of the waste slurry under agent conditioning were studied through laboratory experiments, and the selection and addition amount of the agent were preliminarily determined. Then, the influence of agent addition, stirring time, and pressure filtration time on the pressure filtration efficiency was studied through field experiments. Finally, a method to guide the field filtration time by the indoor model test was put forward.